2023
DOI: 10.1242/jeb.245097
|View full text |Cite
|
Sign up to set email alerts
|

Temporal regulation of temperature tolerances and gene expression in an arctic insect

Abstract: Terrestrial arthropods in the Arctic are exposed to highly variable temperatures that frequently reach cold and warm extremes. Yet, ecophysiological studies on arctic insects typically focus on the ability of species to tolerate low temperatures, whereas studies investigating species’ physiological adaptations to periodically warm and variable temperatures are few. In this study, we investigate temporal changes in thermal tolerances and the transcriptome in the Greenlandic seed bug Nysius groenlandicus, collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…In contrast, Morley et al (2019) showed that polar terrestrial arthropods (>55° latitude) had a high acclimation response for CTmax, but this again was based on two species from the Southern Hemisphere (Alaskozetes antarcticus and Cryptopygus antarcticus). Some work has been done on the heat hardening response (Sørensen et al, 2019) and changes in heat resistance across days in the field of N. groenlandicus (Noer et al, 2022(Noer et al, , 2023. These results…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In contrast, Morley et al (2019) showed that polar terrestrial arthropods (>55° latitude) had a high acclimation response for CTmax, but this again was based on two species from the Southern Hemisphere (Alaskozetes antarcticus and Cryptopygus antarcticus). Some work has been done on the heat hardening response (Sørensen et al, 2019) and changes in heat resistance across days in the field of N. groenlandicus (Noer et al, 2022(Noer et al, , 2023. These results…”
Section: Discussionmentioning
confidence: 98%
“…These studies suggest that hardening responses are marked, and that metabolite levels and RNA expression levels of candidate genes are actively altered on a daily basis (Noer et al, 2022(Noer et al, , 2023. However, none of these studies have addressed responses during long-term acclimation.…”
Section: Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, two other outlier SNPs occur in the CO1 and COIII genes, respectively. Both genes are involved in the mitochondrial electron transport chain, showing transcriptional responses to low temperature tolerance in insects (Huang et al 2017, Noer et al 2023). Overall, our results support the important role of the mitochondria as a center for genes that may be under strong climate-driven selection, resulting in locally adapted populations.…”
Section: Discussionmentioning
confidence: 99%
“…Govaere et al (2019) [11] reported that Leptinotarsa decemlineata can overcome unfavorable winter conditions by increasing keratin and HSP70 expression and adjusting transcription-related processes. Currently, RNA-Seq technology is widely used to study gene expression changes in response to low-temperature stress in multiple insect species, such as Solenopsis japonica [12], Tamarixia radiata [13], Anoplophora glabripennis [14], Calliptamus italicus, Gomphocerus sibiricus [15], Liriomyza trifolii, Liriomyza sativae [16], Callosobruchus chinensis [17], Plutella xylostella [18] and Nysius groenlandicus [19]. These studies have shown that temperature alterations can lead to changes in the expression levels of a range of genes involved in transcription, metabolism, development and especially heat shock proteins.…”
Section: Introductionmentioning
confidence: 99%